In Situ/Operando (Soft) X‐ray Spectroscopy Study of Beyond Lithium‐ion Batteries. Issue 2 (2nd April 2021) - Yang, Feipeng; Feng, Xuefei; Liu, Y.‐Sheng; Kao, Li Cheng; Glans, P.‐A.; Yang, Wanli; Guo, Jinghua
Abstract : The lightweight, rechargeable lithium‐ion battery is one of the dominant energy storage devices globally in portable electronics due to its high energy density, no memory effect, wide operating voltage, lightweight, and good charge efficiency. However, due to safety concerns, the depletion of lithium reserves, and the corresponding increase of cost, an alternative battery system becomes more and more desirable. To develop alternative battery systems with low cost and high material abundance, for example, sodium, magnesium, zinc, and calcium, it is important to understand the chemical and electronic structure of materials. Soft X‐ray spectroscopy, for example, X‐ray absorption spectroscopy (XAS), X‐ray emission spectroscopy (XES), and resonant inelastic soft X‐ray scattering (RIXS), is an element‐specific technique with sensitivity to the local chemical environment and structural order of the element of interest. Modern soft X‐ray systems enable operando experiments that can be applied to amorphous and crystalline samples, making it a powerful tool for studying the electronic and structural changes in electrode and electrolyte species. In this article, the application of in situ/operando (soft) X‐ray spectroscopy in beyond lithium‐ion batteries is reviewed to demonstrate how such spectroscopic characterizations could facilitate the interpretation of interfacial phenomena under in situ/operando condition and subsequent development of the beyond lithium‐ion batteries. Abstract : In this review, the (soft) X‐ray spectroscopies, and their applications in the beyond lithium‐ion battery field are summarized to demonstrate how such spectroscopic characterizations can facilitate the interpretation of interfacial phenomena under in situ/operando condition.